Blended controlled-release nitrogen fertilizer increases rice post-anthesis nitrogen accumulation, translocation and nitrogen-use efficiency - Yuan, Manman; Wu, Gang; Wang, Jiabao; Liu, Chuang; Hu, Yegong; Hu, Run; Zhou, Yan; Zhang, Xiangming; Wang, Wenjun; Sun, Yixiang (Frontiers in Plant Science, 2024)
One-time application of blended controlled-release nitrogen fertilizer (CRN) has the potential to solve the difficulty of top-dressing fertilizer in the cultivation of rice and reduce the cost of CRN fertilizer application. However, its effects on rice dry matter and nitrogen (N) accumulation and translocation, yield and N-use efficiency (NUE) remain uncertain. Field experiments were carried out at three sites (Mingguang, Chaohu, and Guichi) in the Yangtze River Delta in China to compare the effects of the conventional split applications of urea and the blended CRN and on post-anthesis dry matter and N accumulation and translocation, yield, and NUE in rice at 0, 60, 120, 180, and 240 kg N ha -1 . The results showed that at the equal N application rates, compared under the conventional N fertilizer treatment, the blended CRN application significantly increased the rice yield by an average of 0.9-6.9%, mainly due to increase the number of spikelets per panicle. The highest yield achieved with blended CRN treatment occurred at 200 kg N ha -1 , with an NUE of 45.9%. Moreover, in comparison to the conventional N fertilizer, the blended CRN treatment increased pre-anthesis N translocation (Pre-NT) by 1.0-19.8%, and the contribution of pre-NT to grain N by 0.2-8.7%, and NUE by 3.2-28.4%.Meanwhile, the blended CRN treatment reduced labor costs by 1800 Yuan ha -1 and enhanced the economic gains by 21.5-68.8%. Therefore, one-time application of blended CRN ≤ 200 kg N ha -1 application rate improved rice yield, NUE, and economic profit compared to equivalent rates of split applied conventional N fertilizers.